The Effect of Self-Acupressure Therapy on Changes in Blood Pressure in Hypertension Patients - Yenni Monalisa; Edi Purwanto; Lukman Nulhakim (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Hypertension is a silent killer (silent killer). One of the non-pharmacological therapies that can be used is acupressure which is physiotherapy by giving massage and stimulation to certain points on the body. This study aims to determine the effect of self-acupressure therapy on changes in blood pressure in patients with hypertension. Quantitative research type Quasy Experiment with Pre and Post Test Non Equivalent Control Group design. The population is 157 people spread in the working area of the UPT Health Center Tubaan. Non Probability Sampling technique with purposive sampling type. Data were analyzed univariately and bivariately using the Repeated Measures Anova test. The results of the analysis show that the ρ-value = 0.000 <0.05 (Sig.95%). So it can be concluded that there is an effect of giving independent acupressure therapy to changes in blood pressure in people with hypertension. This intervention can be an alternative non-pharmacological therapy used in nursing care for people with hypertension.